Phorbol ester-induced terminal differentiation is inhibited in human U-937 monoblastic cells expressing a v-myc oncogene. - Larsson, L G (1988)
Induction of differentiation of the human monoblastic cell line U-937 in vitro by several physiologic and nonphysiologic inducers is accompanied by a rapid decrease in expression of MYC, the endogenous human myc protooncogene. To investigate whether this reduction is a prerequisite for terminal differentiation, we introduced a constitutively expressed v-myc gene into U-937 cells. The results show that constitutive expression of an avian v-myc oncogene does not interfere with phorbol 12-myristate 13-acetate-induced differentiation of U-937 cells early after stimulation. However, after 24 hr the differentiation process is reversed, as judged by a full recovery of the proliferative capacity and reexpression of the immature phenotype, within the next 2-4 days. We conclude that the terminal stage of macrophage differentiation is inhibited in U-937 cells constitutively expressing a v-myc oncogene.